Pengaruh Ritme Otak dan Musik dalam Proses Belajar - Ellen Prima (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
The brain is an organ that plays an important role in life. Many studies of the brain with various things, one of which is the music and learning process. Some studies use music in brain development to improve concentration and learning. Music is very biased in learning environments to make learning easier and faster if students are relaxed and receptive. The heart rate of people in this state is 60 to 80 times per minute. In this state, his brain runs alpha waves (8-12 Hz), the state of the brain is relaxed but alert for the part of the brain, the hippocampus and somatosensory can work optimally. The purpose of this study is to determine the effect of the rhythm of the brain and music in the learning process. Therefore, this research uses the qualitative method of a descriptive type. The results of this study indicate a link between the rhythm of the brain and music in the learning process.